SISTEM PENDUKUNG KEPUTUSAN PEMBERIAN REWARD KEPADA KARYAWAN MENGGUNAKAN METODE PERBANDINGAN EKSPONENSIAL PADA PT.FIT&FRESH (Information Technology and Telematics, 2015)
Abstraksi Decision Support System Reward  to employees on PT.FIT & FRESH located in Semarang, Semarang precisely in JL.Puri Anjasmoro. During this time the existing system in PT.FIT & FRESH still using manual systems, and often have many obstacles faced them required a long process and complicated, assessment calculation is invalid because it is not using the appropriate formula. Providing Decision Support System Reward For Employees be expanded by using a system of SDLC (system development life cycle), using the programming language PHP and MySQL database. The system is designed to enable managers to make decisions that employees deserve to be given a reward, so that the whole process is done with a system that has been computerized, the method used in this study is a comparison of Exponential method which can take decisions effectively and with a valid calculation. Data collection method used is a field of study that includes interviews or direct FAQ systematically with the manager PT.FIT & FRESH. literature study was also done by reading and studying the books of literature relating to the decision support system. Kata Kunci : Decision Support System, Reward, PHP, MetodeMPE